Ellagic acid protects type II collagen induced arthritis in rat via diminution of IKB phosphorylation and suppression IKB-NF-kB complex activation: in vivo and in silico study - Khan M.A. (2023)
Objective: The present study was designed to explore the potential anti-inflammatory and anti-arthritic effects of ellagic acid (EA) in collagen-induced arthritis (CIA). Methods: CIA rats were treated with MTX (0.25 mg/kg body wt.) and EA (50 mg/kg b.wt.) for a period of 20 days. The effects of treatment in the rats were assessed biochemically by analyzing inflammatory mediators (NF-kB, iNOS, TNF-α, IL-1β, IL-6 and IL-10) and oxidative stress related parameters (MPO, NO, LPO, catalase, SOD, GSH). In addition, we also assessed the expression of some inflammatory mediators TNF-α, CD8 + though immunohistochemistry in the joint tissue. Results: In the present study, we found expression and synthesis of transcription factor NF-kB was prominent in CIA rats. In addition, main pro-inflammatory cytokines such as TNF-α, IL-1β, IL-6, and the anti-inflammatory IL-10, was also stand out. Further, reactive oxygen/nitrogen species was also elevated in CIA rats. Treatment with EA ameliorates all the above mentioned inflammatory and oxidative stress related parameters to near normal. Further, we also confirmed the expression of TNF-α, CD8+ T cells through immunohistochemistry was mitigates in joint tissue of EA treated rats. We find EA significantly inhibited the developmental phase of arthritis. Conclusion: These results suggest that EA act as potent anti-arthritic and anti-inflammatory agent that could be used as a tool for the development of new drug for the treatment of arthritis. Graphical abstract: [Figure not available: see fulltext.]